A new mud lobster of the genus Thalassina Latreille, 1806 (Crustacea: Decapoda: Gebiidea: Thalassinidae) from the mangrove forest of the Cần Giờ Mangrove Reserve, South Vietnam - Marin, Ivan N.; Kolevatov, Vasily M.; Nguyễn, Tuấn Anh (Zootaxa, 2024)
A new species of mud lobster of the genus Thalassina Latreille, 1806 (Decapoda: Gebiidea: Thalassinidae), Thalassina cangioensis sp. nov., is described from mangrove forests of the Cần Giờ Mangrove Biosphere Reserve, located in the Soài Rạp River delta in the downstream of the Dongnai-Saigon River system, South Vietnam. The new species is morphologically mostly similar to T. anomala (Herbst, 1804) in the shape of the rostrum and anterior part of the carapace and the presence of a single median tubercle on pleonal sternites II–V. However, it differs in the strong spinulation on the posterior part of the carapace, the armature of the pereopods I (chelipeds), and the presence of spines on the proximal part of the pleopod I in males. The shape of the pleopod I in males of the new species is mostly similar to that of T. squamifera, but it can be distinguished by the downwardly bulging median part at the tip, which is unique to the genus. Molecular genetic analysis revealed that the new species strongly genetically diverged (by the mitochondrial COI gene marker) from all currently sequenced species of the genus Thalassina, such as T. anomala, T. gracilis, T. kelanang and T. squamifera.